2003
DOI: 10.1089/107999003765027375
|View full text |Cite
|
Sign up to set email alerts
|

Immunologic Effects of Intermediate-Dose IL-2 i.v. After Autologous Hematopoietic Cell Transplantation in Pediatric Solid Tumors

Abstract: Adoptive immunotherapy with interleukin-2 (IL-2) may control minimal residual disease (MRD) and prevent relapse after autologous hematopoietic cell transplantation (AHCT). The objective of this study was to determine the immunologic effects of intermediate doses of intravenous (i.v.) IL-2 after AHCT in children with poor-prognosis solid tumors. Eleven patients received a median five cycles consisting of escalating doses of IL-2 i.v. for 5 days after a median time interval of 94 days post-AHCT. The phenotype of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2005
2005
2019
2019

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 16 publications
(9 citation statements)
references
References 16 publications
(31 reference statements)
0
9
0
Order By: Relevance
“…Treatment of patients with breast cancer and lymphoma using IL-2 was shown to significantly increase numberofcirculatingNKcellsandtheircytotoxicityagainstNKresistantbreastcancer and lymphoma cell lines 183 . Many other similar studies on immunostimulation in cancer patients have made similar observations where IL-2 infusions induce an increaseinwhitebloodcellcounts,increaseincirculatingTcellsandmostlyCD56 bright NKcells,elevatedcytotoxicactivityofNKcells [184][185][186] .Yet,suchstudieshaveprimarily shown only temporary responses leading to eventual tumor relapse and no survival improvement.…”
Section: Il-2alonementioning
confidence: 85%
“…Treatment of patients with breast cancer and lymphoma using IL-2 was shown to significantly increase numberofcirculatingNKcellsandtheircytotoxicityagainstNKresistantbreastcancer and lymphoma cell lines 183 . Many other similar studies on immunostimulation in cancer patients have made similar observations where IL-2 infusions induce an increaseinwhitebloodcellcounts,increaseincirculatingTcellsandmostlyCD56 bright NKcells,elevatedcytotoxicactivityofNKcells [184][185][186] .Yet,suchstudieshaveprimarily shown only temporary responses leading to eventual tumor relapse and no survival improvement.…”
Section: Il-2alonementioning
confidence: 85%
“…In the pediatric population, IL-2 is most noted for its success in high-risk neuroblastoma when combined with an anti-GD2 monoclonal antibody and granulocyte-macrophage colony-stimulating factor (GM-CSF). Unfortunately, many other studies utilizing IL-2 have shown no antitumor effects [ 31 , 32 ]. Schwinger et al investigated high-dose IL-2 in patients with heavily pre-treated solid tumors after resection of primary and/or metastatic lesions in an attempt to maintain remission.…”
Section: Immunostimulatory Agentsmentioning
confidence: 99%
“…25,26 In brief, fluorescent DiOC 18 3 -stained K562 cells were gated and propidium iodide-stained cells emitting red fluorescence were evaluated for percentage of lysis.…”
Section: Nk Cytotoxicity Assaymentioning
confidence: 99%